2019
DOI: 10.21203/rs.2.18801/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The expression of the gene associated with β-glucan content, β-amylase and limit dextrinase synthesis as affected by post-heading heat stress in barley

Abstract: Background: Malt barley shows a dramatic deterioration of malt quality when exposed to heat or high temperature stress during grain-filling stage (post heading), and global change results in the more frequent occurrence of high temperature, posing a severe threat to high-quality malt barley production. In a previous study, we found heat stress during grain-filling stage caused the significant reduction of kernel weight, and the significant increase of protein and β-glucan content, and βamylase and limit dextri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Ni et al. (2019) studied the relative expression of HvCslF6 in two barley cultivars (Hua30 and ZU9) at 32°C during the early and late grain filling stages. A significant increase in the relative expression of HvCslF6 was noticed in both cultivars under heat stress compared to the control temperature (24°C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni et al. (2019) studied the relative expression of HvCslF6 in two barley cultivars (Hua30 and ZU9) at 32°C during the early and late grain filling stages. A significant increase in the relative expression of HvCslF6 was noticed in both cultivars under heat stress compared to the control temperature (24°C).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been shown that the overexpression of CslF6 gene caused a greater than 80% increase in 1,3;1,4β-glucan in transgenic barley grains (Burton et al, 2011). Ni et al (2019) studied the relative expression of HvC-slF6 in two barley cultivars (Hua30 and ZU9) at 32˚C during the early and late grain filling stages. A significant increase in the relative expression of HvCslF6 was noticed in both cultivars under heat stress compared to the control temperature (24˚C).…”
Section: β-Glucan Biosynthesis Pathway Genesmentioning
confidence: 99%